Penguatan Jiwa Wirausaha melalui Pelatihan Pembuatan Dimsum di Panti Asuhan Tahfidz Hidayah - Saputra, Maskhur Dwi; Haetami, Ahmad; Riyadi, Sugeng (Universitas Pahlawan Tuanku Tambusai, 2025)
This community service activity aims to strengthen the entrepreneurial spirit of the students (santri) at the Hidayah Tahfidz Orphanage through a dimsum making training program. The activity was carried out using a hands-on method, in which the participants practiced making dim sum under the guidance of the community service team. The ingredients, equipment, and step-by-step instructions were provided by the team. The final outcome of this activity was the successful preparation of cooked dim sum, which was then evaluated by the community service team. Based on the evaluation, Group 1 received a final score of 88.33, Group 2 scored 78.33, Group 3 scored 80, and Group 4 scored 78.33. Furthermore, regarding the results of the dim sum knowledge test, the overall final score of the students at the Hidayah Tahfidz Orphanage was 73.5, which falls into the 'fairly good' category. Therefore, it can be concluded that the students at the Hidayah Tahfidz Orphanage are reasonably capable of making dim sum based on the knowledge they have acquired.